The Pedagogical Value of Student Conferences: A Study on Descriptive Text Instruction in Culinary Art Education - Chintia Budi Amelia; Fardini Sabilah; Sri Hartiningsih (VELES Voices of English Language Education Society, 2023)
Teaching English within the culinary arts is challenging for many instructors. The field of culinary arts has its specialized terminology and distinct context, which sets it apart from general English teaching. In light of this, the English for Specific Purposes (ESP) program was introduced. ESP is designed to align English instruction with the specific needs of students in culinary studies, ensuring they are prepared academically and for their future roles in the industry. This research examines the effectiveness of student conferences in teaching descriptive texts, an essential aspect of culinary studies. Data collection involved interviews, classroom observations, and document reviews. The results were encouraging: student conferences emerged as a potent tool, leading to significant improvements in students' writing and comprehension abilities. When combined with the ESP approach, there was a notable increase in student motivation and engagement. These findings offer educators enhanced strategies for specialized English teaching in the culinary arts. Moreover, this study serves as a stepping stone for further research, aiming to refine English instruction in specialized domains.